Common clonal origin of conventional T cells and induced regulatory T cells in breast cancer patients - Xydia, Maria; Rahbari, Raheleh; Ruggiero, Eliana; Macaulay, Iain; Tarabichi, Maxime; Lohmayer, Robert; Wilkening, Stefan; Michels, Tillmann; Brown, Daniel; Vanuytven, Sebastiaan; Mastitskaya, Svetlana; Laidlaw, Sean; et al. (Nature Communications, 2021)
Regulatory CD4+ T cells (Treg) prevent tumor clearance by conventional T cells (Tconv) comprising a major obstacle of cancer immune-surveillance. Hitherto, the mechanisms of Treg repertoire formation in human cancers remain largely unclear. Here, we analyze Treg clonal origin in breast cancer patients using T-Cell Receptor and single-cell transcriptome sequencing. While Treg in peripheral blood and breast tumors are clonally distinct, Tconv clones, including tumor-antigen reactive effectors (Teff), are detected in both compartments. Tumor-infiltrating CD4+ cells accumulate into distinct transcriptome clusters, including early activated Tconv, uncommitted Teff, Th1 Teff, suppressive Treg and pro-tumorigenic Treg. Trajectory analysis suggests early activated Tconv differentiation either into Th1 Teff or into suppressive and pro-tumorigenic Treg. Importantly, Tconv, activated Tconv and Treg share highly-expanded clones contributing up to 65% of intratumoral Treg. Here we show that Treg in human breast cancer may considerably stem from antigen-experienced Tconv converting into secondary induced Treg through intratumoral activation.
CRIS-Team Scopus Importer:2023-03-23